Pengaruh Pendidikan Terhadap Pembentukan Jiwa Agama - sudarto, sudarto sudarto (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2018)
Someone good or bad will come from several factors which they found from their education. Education is an appropriate means to achieve it. Especially as Muslims the Islamic education would become a path that must be taken by all the people. Religious education is a form of educational value, because it is the maximum and the absence of religious education depends on factors that can motivate to understand the value of religion. Moreover the atmosphere of religious education made at home then the development of religious life will be able to grow optimally. A person's psychological development is a form of fairness and do occur in a person. Therefore, education is a necessity in directing the process of psychological development. Moreover, in the educational institutions of Islam, will certainly affect the formation of religious life. The religious soul needs to be instilled in children from an early age.